Face Experience and the Attentional Bias for Fearful Expressions in 6- and 9-Month-Old Infants - Safar, Kristina; Kusec, Andrea; Moulson, Margaret C. (Frontiers in Psychology, 2017)
Infants demonstrate an attentional bias towards fearful facial expressions that emerges in the first year of life. The current study investigated whether this attentional bias is influenced by experience with particular face types. Six-month-old (n=33) and 9-month-old (n=31) Caucasian infants’ spontaneous preference for fearful facial expressions when expressed by own-race (Caucasian) or other-race (East Asian) faces was examined. Six-month-old infants showed a preference for fearful expressions when expressed by own-race faces, but not when expressed by other-race faces. Nine-month-old infants showed a preference for fearful expressions when expressed by both own-race faces and other-race faces. These results suggest that how infants deploy their attention to different emotional expressions is shaped by experience: Attentional biases might initially be restricted to faces with which infants have the most experience, and later be extended to faces with which they have less experience.